Modified spiht algorithm for quincunx wavelet image coding - Ismahane Benyahia; Abdesselam Bassou; Chems El Houda Allaoui; Mohammed Beladgham (Institute of Advanced Engineering and Science, 2019)
In this paper, an image compression method based on the Quincunx algorithm coupled with the modified SPIHT encoder (called SPIHT-Z) is presented. The SPIHT-Z encoder (coupled with quincunx transform) provides better compression results compared with two other algorithms: conventional wavelet and quincunx both coupled with the SPIHT encoder. The obtained results, using the algorithm that applies (Quincunx with SPIHT-Z) are evaluated by image quality evaluation parameters (PSNR, MSSIM, and VIF). The compression results on twenty test images showed that the proposed algorithm achieved better levels of the image evaluation parameters at low bit rates.